Highly Stretchable Micro‐Supercapacitor Arrays with Hybrid MWCNT/PANI Electrodes. Issue 3 (30th January 2017) - Li, La; Lou, Zheng; Han, Wei; Chen, Di; Jiang, Kai; Shen, Guozhen
Abstract : Stretchable energy storage devices are required to fit for stretchable electronic devices, forming a fully stretchable system for comfortable and body‐attachable electronic devices. Herein, highly stretchable micro‐supercapacitors are fabricated by designing wave‐shaped hybrid multiwalled carbon nanotubes/polyaniline electrodes. As‐fabricated stretchable devices exhibit a large areal capacitance of 44.13 mF cm −2 and offer a power density of 0.07 mW cm −2 at an area energy density of 0.004 mW h cm −2 . Owing to the designed wavy electrode structure, the electrochemical performances of the stretchable micro‐supercapacitors are almost invariably under different stretching stations ranging from 5% to 40%. By fabricating stretchable micro‐supercapacitors arrays, a red light‐emitting diode can be easily lighted under different conditions including stretching, twisting, crimping, and winding. All these results confirm the outstanding stability and mechanical strength of stretchable micro‐supercapacitors, demonstrating its potential application in skin‐patchable electronics or portable/wearable devices. Abstract : Stetchable micro‐supercapacitor arrays are fabricated with polyaniline (PANI) nanorods coated multiwalled carbon nanotubes as the electrode, which present stable performance and long‐term stability under stretching, twisting, crimping, and winding and will pave the way for advanced applications in skin‐patchable electronics or portable/wearable devices.